2014
DOI: 10.1172/jci75181
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 controls sympathetic arterial innervation

Abstract: Autonomic sympathetic nerves innervate peripheral resistance arteries, thereby regulating vascular tone and controlling blood supply to organs. Despite the fundamental importance of blood flow control, how sympathetic arterial innervation develops remains largely unknown. Here, we identified the axon guidance cue netrin-1 as an essential factor required for development of arterial innervation in mice. Netrin-1 was produced by arterial smooth muscle cells (SMCs) at the onset of innervation, and arterial innerva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 60 publications
1
79
0
7
Order By: Relevance
“…The glial-derived neurotrophic factor (GDNF) family member artemin, and the neurotrophins Nerve growth factor (NGF) and neurotrophin-3 (NT-3) are expressed in embryonic arterial SMCs, and inactivation of the genes encoding these molecules in mice leads to defects in sympathetic axon growth and extension along the arterial vasculature 39, 40 . Postnatal arterial SMCs acquire the expression of the axon guidance molecule netrin-1, which is required for innervation of arterial SMCs by sympathetic neurons 41 .…”
Section: Arteriogenesis In Developmentmentioning
confidence: 99%
“…The glial-derived neurotrophic factor (GDNF) family member artemin, and the neurotrophins Nerve growth factor (NGF) and neurotrophin-3 (NT-3) are expressed in embryonic arterial SMCs, and inactivation of the genes encoding these molecules in mice leads to defects in sympathetic axon growth and extension along the arterial vasculature 39, 40 . Postnatal arterial SMCs acquire the expression of the axon guidance molecule netrin-1, which is required for innervation of arterial SMCs by sympathetic neurons 41 .…”
Section: Arteriogenesis In Developmentmentioning
confidence: 99%
“…22 The newly specified arteries recruit smooth muscle cells that induce noradrenergic differentiation of sympathetic progenitors 58 and promote extension and growth of sympathetic nerve fibers along the arteries and eventually arterial innervation. 59,60 Innervation occurs during late gestation in avian embryos, which are fully motile at birth, whereas it occurs postnatally in mice, 60 which remain immature and acquire full motility only about postnatal day 10. Catecholamine release in turn contributes to maintenance of arterial fate, revealing a positive feedback loop between nerve-induced arterial function and arterial morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Additionally, a recent study has shown that netrin-1 and its receptor, DCC, control sympathetic arterial innervation and play an important role in the regulation of the blood flow to peripheral organs. 19 Moreover, netrin-1 binding to specific receptors like DCC has been shown to activate multiple pathways including MAPKs, PKC, src, Rac and Rho kinase, and focal adhesion kinase 2022 , which all have been previously reported to be associated with HTN and BP regulation. 2325 Furthermore, a recent study has demonstrated that netrin-1 activates PRKC alpha , and FAK/Fyn, which are important for the activation of the ERK, JNK and NF-kB.…”
Section: Discussionmentioning
confidence: 99%